COVID-19 ASSOCIATED CAVERNOUS SINUS THROMBOSIS: 2-YEAR FOLLOW-UP EXPERIENCE - Erkin N. Bilalov; Okilkhon I. Oripov; Ravshan Z. Umarov; Gulomboy U. Khudaibergenov; Bakhodir E. Bilalov (Central Asian Journal of Medicine, 2023)
This article presents the experience gained over the past 2 years of the coronavirus infection pandemic in monitoring patients with COVID-19 associated cavernous sinus thrombosis. The article describes the results of studies and observations of domestic specialists who worked with these patients. The first descriptions of clinical cases of COVID-19 associated cavernous sinus thrombosis in Uzbekistan and their specific features are given. The results of a comparative analysis of the clinical course of this pathology with classical archival cases of cavernous sinus thrombosis are discussed. The main factors that are associated with the development of complications in patients with coronavirus infection and their frequency of occurrence are listed. Separately, the results of studies by domestic authors devoted to the development of optimal methods for early diagnosis are presented.